Cassava Donuts: Community Economic Empowerment Through Making and Marketing - Putriani, Erika; Mujahidin, Anwar (CV. BImbingan Belajar Assyfa, 2023)
Cassava is an example of an agricultural product that needs to be processed properly. The average population, especially homemakers, needs work to supplement household income due to the coronavirus (COVID-19) outbreak, which has greatly affected people's economic lives, so by optimizing village potential, community economic empowerment in Purwosari Babadan Village, Ponorogo Regency. This community service aims to help the community's economy through community abilities and skills, which creates opportunities for home industry businesses to be independent and not dependent on government assistance. Cassava fruit can be used to support food diversification through various processing processes. The successful growth of this diversity can increase sales value so that it has a positive impact on community welfare. Cassava is usually processed by community organizations using traditional processes such as steaming or frying, although this approach cannot be verified. One of the reasons for the minimal processing of this product is the need for a deeper understanding of the differences in processing methods, packaging technology as a business opportunity, and how to advertise it online.